Analisis Pengolahan Limbah Padat Tahu Terhadap Alternatif Industri Pangan Sosis (Grade B) - Ibnu Sina; Untung Nugroho Harwanto; Zakki Rosmi Mubarok (Program Studi Teknik Kimia, Universitas Pamulang, 2021)
Literature studies show that the nutrient content in tofu pulp is still high; however the utilization of this waste is still relatively low by the community. Nowadays, tofu dregs is still widely used as an ingredient for animal feed. Some of the reasons why people don't take advantage of tofu waste are consits of the funding, equipment, time and worries related to starting their own business. The aims of this study is to make a pre-designed tofu dregs processing plant into a multipurpose product aggregate such as sausages driven by the tofu business community. The method stage in this research is making a feasible product and process scheme, analyzing tofu solid waste in the form of a paper project and making a household scale sausage production prototype. The results of this study are able to produce a role model for tofu dregs utilization which is more conomically valuable but still meet the standard and quality of reasonableness. The results of the role model will be disseminated by reaching out to tofu entrepreneur communities to collaborate with each other so that the utilization of tofu with high economic value can be carried out more massively, structurally and systematically.